Molecular mechanism of the synaptotagmin–SNARE interaction in Ca(2+)-triggered vesicle fusion - Vrljic, Marija (2010)
In neurons, SNAREs, synaptotagmin, and other factors catalyze Ca(2+)-triggered fusion of vesicles with the plasma membrane. The molecular mechanism of this process remains an enigma, especially regarding the interaction between synaptotagmin and SNAREs. Here we characterized this interaction by single-molecule fluorescence microscopy and crystallography. The two rigid Ca(2+)-binding domains of synaptotagmin 3 undergo large relative motions in solution. Interaction with SNARE complex amplifies a particular state of the two domains that is further enhanced by Ca(2+). This state is represented by the first SNARE-induced Ca(2+)-bound crystal structure of a synaptotagmin fragment containing both domains. The arrangement of the Ca(2+)-binding loops of this structure of synaptotagmin 3 matches that of SNARE-bound synaptotagmin 1, suggesting a conserved feature of synaptotagmins. The loops resemble the membrane-interacting loops of certain viral fusion proteins in the postfusion state, suggesting unexpected similarities between both fusion systems.